Digital Technology Utilizer Strategy to Promote Manila Sapodilla Seed Oil Extract Emulsion Product as A Hair Growth Product - Fatta, Chika Apselia; Subagja, Iwan Kurniawan; Hakim, Azis (Dinasti Publisher, 2025)
Using digital technology is an important step in promoting Manila Sapodilla Seed Oil Extract Emulsion as a product that helps with hair growth in today's world. Social media and online platforms are now key tools for reaching more people and building connections with consumers. This study looks at existing research on how digital promotion works for beauty and hair care products. The findings indicate that utilizing social media platforms like TikTok and Instagram, combined with strategies such as electronic word of mouth (eWOM), collaborating with influencers, and enhancing website performance, can increase brand recognition and foster greater consumer interest in purchasing the product. Also, new product features, eye-catching packaging, and engaging online interactions help build a better image and trust in the product. Therefore, a promotional plan based on digital technology is effective in introducing and growing the Manila Sapodilla Seed Oil Extract Emulsion in a competitive market.